(untitled) - Chandor, Anthony (Harmondsworth, 1977)
This book is a glossary of some 3000 words, phrases and acronyms used in connection with computers.
Keywords: Electronic data processing,Electronic digital computers,Xử lý dữ liệu điện tử,Kỹ thuật số máy tính điện tử